Review of Exploring the Future of Prosthetics Using Osseointegration Technology - Abbas, Saif M.; Takhakh, Ayad M.; Chiad, Jumaa S. (Al-Nahrain Journal for Engineering Sciences, 2023)
Additionally, it has been demonstrated that osseointegrated implantation offers superior proprioception and control over the prosthesis, enabling more natural movement and improved functional results. Additionally, it lowers the chance of falling and increases energy transfer efficiency, making it simpler for amputees to engage in physical activity. Furthermore, as compared to conventional socket prosthesis attachment, osseointegrated implantation has been linked to higher patient satisfaction and quality of life._x000D_ It is crucial to remember that osseointegration is a surgical operation with risks including infection and implant failure. Additionally, for effective implantation, it needs a specific amount and quality of bone, which may restrict its usage in some individuals. Furthermore, osseointegrated implantation could be more expensive than conventional socket prosthetics._x000D_ Understanding the efficacy and safety of this method requires research on complication rates and outcome metrics in patients having osseointegrated prosthesis implantation. You may acquire information on things like infection rates, implant failure, patient satisfaction, and functional results by studying original research papers. Clinical decision-making can then be improved with the use of this information._x000D_ In transfemoral amputees, osseointegration has showed promise as a powerful substitute for socket prostheses. A growing corpus of research has shown that osseointegrated implantation provides advantages in terms of increasing mobility, decreasing discomfort, and improving general quality of life. The efficiency of osseointegration for transtibial and upper extremity implants has received little attention._x000D_ Minor soft tissue infections are the most frequent consequences, although they are manageable with the right treatment and monitoring. To further reduce the risk of problems and improve the overall success of osseointegrated implantation, research and development are ongoingly focused on enhancing surgical methods and implant design._x000D_ Although osseointegration has a lot of potential, not all amputees may be good candidates for it. Considerations for osseointegrated implantation must take into consideration elements including the degree and nature of the amputation, the quality and density of the bone, and the desires of the patient.